Два новых для фауны СССР вида ящериц из семейства гекконов - Горелов, Ю.К.; Даревский, И.С.; Щербак, Н.Н. (Вестник зоологии, 1974)
Alsophylax tuberculatus Blanf. found in the Badkhyz reservation in the South of Turkmenia in 1972 is mentioned first for the USSR fauna. Together with some other West-Asian species this one belongs to the subgenus Bunopus, the representatives of which are 'characterized by the presence of regularly distributed enlarged dorsal tubercles. The species with tubercles scattered in disorder or those without tubercles at all belong to the subgenus Alsophylax s. str. The species Gymnodactylus microlepis from the Tedjen river valley in South Turkmenia described by Lantz, 1918 is the subspecies of the Iran species G. longipes Nik. from which the former differs only in relatively shorter legs. As a whole, this spe- cies is characterized either by the absence of a suture or by a slightly developed con- tact between the first pair of the mandibular shields behind the apex of the mental one.